Comprehensive insights into uveal melanoma – risk factors, pathophysiology, prognosis, and diagnostic approaches - Paduszyńska, Natalia; Dąbrowska, Anna; Gonciarz, Marta Justyna; Zaliwska, Dominika; Czach, Magdalena; Strojny, Agnieszka Aleksandra; Adamiec, Dominika Karolina; Kraszkiewicz, Adrianna; Kamińska, Monika Anna; Do, Monika Kienanh (Quality in Sport, 2024)
Introduction and purpose Uveal melanoma is the most common primary intraocular neoplasm in adults, which originates from melanocytes and arises from the choroid, ciliary body, or iris. The range of symptoms is wide but there are also asymptomatic cases. Metastases mainly concern the liver, and their occurrence significantly worsens the prognosis. Therefore, early detection is so crucial. This article summarizes significant information regarding epidemiology, pathophysiological processes, and genetic abnormalities underlying the disease. Moreover, we highlight possible clinical manifestations and discuss currently applied diagnostic methods. Description of the state of knowledge The average annual incidence worldwide is 6 cases per million. Risk stratification takes into account mutations, chromosomal abnormalities, tumor size, or invasion of adjacent tissues. In clinical practice, several diagnostic modalities are available, such as gonioscopy, indirect ophthalmoscopy, fundus photography, ultrasound biomicroscopy, ocular ultrasonography, optical coherence tomography, angiography, computed tomography, magnetic resonance, and positron emission tomography. Conclusions The publications analyzed in this article have shown that uveal melanoma is quite a medical challenge. Understanding the disease pathogenesis and underlying genetic abnormalities that may be the target of drugs, could be of great importance for patients and may constitute a step towards a personalized approach. However, further research is necessary to recognize cancer mechanisms more precisely, expand diagnostic options, and consequently register targeted drugs and develop comprehensive management guidelines, especially for metastatic disease to achieve improved survival outcomes.